USE OF SUPERCONDUCTOR TECHNOLOGY IN HIGH SPEED ELECTRICAL DISTRIBUTION NETWORKS - Muhammad Firdaus; Melly Angglena; Sri Widiastuti; Usman Tahir; Som Chai (Journal of Moeslim Research Technik, 2025)
The increasing demand for efficient and reliable electricity distribution necessitates innovative technologies. Superconductors, known for their ability to conduct electricity without resistance, present a promising solution for enhancing power transmission. Their implementation in high-speed electric distribution networks could revolutionize energy efficiency and reliability. This research aims to evaluate the feasibility and benefits of integrating superconducting technology into high-speed electricity distribution systems. The study seeks to identify the performance improvements and potential challenges associated with this technology. A mixed-methods approach was employed, combining theoretical analysis with practical simulations. The performance of superconducting cables was compared to conventional copper and aluminum cables under varying load conditions. Key metrics, including efficiency, energy loss, and thermal performance, were assessed using advanced simulation software. The findings indicate that superconducting cables can achieve up to 90% efficiency, significantly reducing energy losses compared to traditional materials. Simulations demonstrated that superconductors can handle higher power loads with minimal thermal issues, making them suitable for high-speed distribution networks.